THE INFLUENCE OF MOTIVATION AND COMPENSATION AND SATISFACTIONWORK ON EMPLOYEE PERFORMANCE AT BRANCH RANKING GUIDANCEBUILDING PURBA DELI SERDANG - Hendri Mayanta Tarigan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study aims to determine the effect of motivation and compensation and job satisfaction on employee performance. This research is a type of quantitative research. The population in this study amounted to 15 employees and the sample numbered 15 respondents who were taken using a saturated sampling technique. This research was conducted at the Ranking Tutoring of the Bangun Purba Branch, Deli Serdang, using secondary data obtained through distributing questionnaires. The data analysis technique used in this study is multiple linear regression and is operated through SPSS 21.0. The results of this study indicate that motivation as well as compensation and job satisfaction affect employee performance. While motivation as well as compensation and job satisfaction simultaneously influence employee performance.